Learning to Be 'Uncivil': Class Formation and Feminisation in the Public Service Alliance of Canada, 1966-1996 - Warskett, Rosemary Elizabeth (Carleton University, 1998)
What kinds of associations did Canadian 'civil servants' form in the postwar period? Why and how did they learn to become 'uncivil', transforming themselves into militant unionists during the 1980s and 1990s? These questions are addressed theoretically and empirically through a case study of the Public Service Alliance of Canada (PSAC). In 1966, PSAC leaders adopted a consultative, harmonious approach to staff relations, organizing the newly formed union to reflect the federal civil service's structure and practice. Class and gender divisions were submerged, hidden beneath the historical and ideological construction of the civil service as a distinctive, politically neutral category. Cracking apart of the unity of federal 'civil servants' began to occur in the 1960s. Class and gender divisions started to come to the fore with the expansion of the Canadian federal state, the increase of women in administrative support roles, and the enactment of collective bargaining rights. During the 1970s and 1980s, working class formation and capacity developed within the Canadian labour movement in concert with feminism, even though the legal structuring of labour relations continued to limit this class and gender formation. In this respect the Public Service Staff Relations Act and the Public Service Employment Act continued to reproduce the practices of the social category of civil servants. Nevertheless, within the PSAC, collective bargaining, the right to strike and the pay equity provisions of the Canadian Human Rights Act produced openings for learning and strategizing around subordinate class and gender issues and demands. Predominately female clerical workers, successfully challenged the structure and practices of the traditional 'civil service' associations. They learned to strategize and to incorporate a working class, feminist discourse into the union's practices. In the process the demand for pay equity was redefined and transformed into a demand of wage equity for all members, thus becoming a source of solidarity during the PSAC's 1991 general strike. PSAC activists learned to use openings in state structures to transform union agency, despite the existence of a legal regime that continues to constrain the development of working class and feminist capacities.
Keywords: Social sciences